2005
DOI: 10.1196/annals.1342.054
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Parameter kmaxin Fractal Analysis of Rat Brain Activity

Abstract: We recorded electrocortical activity in anesthetized rats and constructed k(max) new self-similar time series, applying Higuchi's algorithm. The aim of this study was to estimate value of the parameter k(max) in order to obtain fractal dimension values as an optimum measure of biosignal change. After our analysis, electrocortical activity recordings resulted in a family of curves f(k(max)). Three regions could be distinguished 2 < or = k(max) < 8, with a U-shape; 8 < or = k(max) < or = 30, with a steeper quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Parameter N = 200 was within the range used by other authors and was equivalent to an epoch (window) duration of 0.8 s at the sampling rate of 256 s −1 . We have chosen k max = 8 on the basis of our recent study [6] on the optimum choice of k max value. Individual FD values were averaged across all epochs for particular experimental conditions to obtain the mean FD.…”
Section: Methodsmentioning
confidence: 99%
“…Parameter N = 200 was within the range used by other authors and was equivalent to an epoch (window) duration of 0.8 s at the sampling rate of 256 s −1 . We have chosen k max = 8 on the basis of our recent study [6] on the optimum choice of k max value. Individual FD values were averaged across all epochs for particular experimental conditions to obtain the mean FD.…”
Section: Methodsmentioning
confidence: 99%
“…They justified this correlation with the idea that EEG can reflect cortical dynamics and demonstrates change in response to brain injury and ischemic events. Using the Higuchi algorithm to compute the FD, this study found that after the first acute injury, there is a reversible increase in FD, but after the third repeated injury, the increase becomes irreversible (Spasic et al, 2005a(Spasic et al, ,b, 2008. Therefore, fractal analysis can be used to differentiate between initial and repeated injury.…”
Section: Electroencephalogrammentioning
confidence: 96%
“…According to the study [37], the optimum range of k max was 8 \ k max \ 18. The value k max = 8 as the minimum in that range was used for the fractal analysis of electrocortical activity.…”
Section: The Calculation Of Fractal Dimensionsmentioning
confidence: 99%
“…The fractal dimension (FD) values of recorded, nonlinear and in the wide sense stationary sequences of up to 241 s (divided into epochs of 781 ms, without overlap) were calculated off-line by the original Higuchi algorithm [19] and slightly modified one [37], (DFHIG and DFHIGK programs). We shall briefly describe this algorithm which is one of the most accurate methods for the determination of fractal dimensions.…”
Section: The Calculation Of Fractal Dimensionsmentioning
confidence: 99%